Effectiveness of Endurance Training Based on Small-Sided Games Model for Beginner Women Futsal - Ramdan Pelana; Aan Wasan; Ayu Purnama Wenly (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to see the effectiveness of endurance training based on small-sided games models for female futsal begginer players. The subject of the study is 12 beginner female futsal players from Padang Futsal Academy aged 19-23 years. The endurance variables are measured before and after endurance training based on small-sided games program is given. Research instruments using Multi Stage Fitness Test (MSFT). The results of the pre-test analysis were an average value of 28.6 ml/kg/min, the highest value of 31.4 ml/kg/min, the lowest value of 25.2 ml/kg/minute. Furthermore, the results of post-test analysis were the average data value of 37.9 ml/kg/min, the highest value of 41.1 ml/kg/min, the lowest value of 36.2 ml/kg/min. Test paired Sample T-Test through SPSS.26 application obtained Sig value. (2-tailed) of 0.000 < 0.05, it was concluded that there is an average difference between pre-test and post-test in Padang Futsal academy athletes in Padang City. Then, the mean difference between pre-test and post-test is 7.6417. This finding shows that the endurance training based on small-sided games programs has a significant effect on the performance variables of endurance in Padang Futsal Academy athletes in Padang City.